Network exposure and excessive use of force: investigating the social transmission of police misconduct - Ouelle, Marie (Criminology & public policy, 2019)
In this study, we investigate how a police officer's exposure to peers accused of misconduct shapes his or her involvement in excessive use of force. By drawing from 8,642 Chicago police officers named in multiple complaints, we reconstruct police misconduct ego‐networks using complaint records. Our results show that officer involvement in excessive use of force complaints is predicted by having a greater proportion of co‐accused with a history of such behaviors.